1984
DOI: 10.1002/bit.260261204
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Pseudomonas aeruginosa in biofilms: Steady state

Abstract: Aerobic glucose metabolism by Pseudomonas aeruginosa in steady-state biofilms at various substrate loading rates and reactor dilution rates was investigated. Variables monitored were substrate (glucose), biofilm cellular density, biofilm extracellular polymeric substance (EPS) density, and suspended cellular and EPS concentrations. A mathematical model developed to describe the system was compared to experimental data. Intrinsic yield and rate coefficients included in the model were obtained from suspended con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
2
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(76 citation statements)
references
References 8 publications
(1 reference statement)
2
66
2
2
Order By: Relevance
“…Rittmann (1982) found in the prior research that when other parameters were constant, the speed of biofilm detachment was proportional to 0.58 power of sheer stress. Bakke et al (1984) found that there was linear relationship between detach speed of biofilms and sheer stress. Horn et al (2003) deemed that the detachments of biofilms were the results of both fluid sheer stress and intensity of biofilm.…”
Section: Discussionmentioning
confidence: 97%
“…Rittmann (1982) found in the prior research that when other parameters were constant, the speed of biofilm detachment was proportional to 0.58 power of sheer stress. Bakke et al (1984) found that there was linear relationship between detach speed of biofilms and sheer stress. Horn et al (2003) deemed that the detachments of biofilms were the results of both fluid sheer stress and intensity of biofilm.…”
Section: Discussionmentioning
confidence: 97%
“…Authors studying wastewaters and industrial waters are divided between those who defend that the activity of sessile and planktonic bacteria is similar (Bakke et al, 1984;Characklis and Marshall, 1990) and those who reached opposite conclusions (Plas et al, 1994;Le Magrex et al, 1994). Quantitative data on bacterial growth kinetics in drinking water systems is scarce (Pedersen, 1990;Block et al, 1993;Boe-Hansen et al, 2002b), although such data would seem important for the proper design of distribution networks and reservoirs.…”
Section: Article In Pressmentioning
confidence: 99%
“…The density of planktonic bacteria may be driven quite low by the antibiotic but one expects that the wallattached cell density is largely unaffected. Thus we conclude that if (8) holds then introduction of antibiotic into the flow reactor will not be effective in eradicating the bacteria.…”
Section: The Factors G and T Have Natural Biological Interpretationsmentioning
confidence: 86%
“…Simple models do not attempt to provide much detail on the spatial structure of biofilms but aim to provide information on conditions suitable for biofilm establishment and maintenance and which model the formation of biofilms directly, starting from an inoculum of planktonic bacteria. Among the more widely known of these, we mention Topiwala and Hamer [55], Baltzis and Fredrickson [7], Bakke et al [8], and Pilyugin and Waltman [45]. Less known is the work of R. Freter and his group (Freter [25,24] and Freter et al [26,27]), who formulated a mathematical model to understand the phenomena of colonization resistance in the mammalian gut (stability of resident microflora to colonization).…”
mentioning
confidence: 99%